2024
DOI: 10.1186/s12889-024-17907-1
|View full text |Cite
|
Sign up to set email alerts
|

Clearing the air: evaluating institutions’ social media health messaging on wildfire and smoke risks in the US Pacific Northwest

Catherine E. Slavik,
Daniel A. Chapman,
Alex Segrè Cohen
et al.

Abstract: Background Wildfire smoke contributes substantially to the global disease burden and is a major cause of air pollution in the US states of Oregon and Washington. Climate change is expected to bring more wildfires to this region. Social media is a popular platform for health promotion and a need exists for effective communication about smoke risks and mitigation measures to educate citizens and safeguard public health. Methods Using a sample of 1,28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Furthermore, social media application for broader societal communication has been examined in contexts such as health risk management and public sentiment during crises. Slavik et al [50] demonstrated how social media platforms were crucial in disseminating timely and accurate information about health risks, such as wildfire smoke, to the public. Similarly, Qi et al [42] analyzed public sentiment during the COVID-19 lockdowns, revealing valuable insights into public attitudes that could inform government policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, social media application for broader societal communication has been examined in contexts such as health risk management and public sentiment during crises. Slavik et al [50] demonstrated how social media platforms were crucial in disseminating timely and accurate information about health risks, such as wildfire smoke, to the public. Similarly, Qi et al [42] analyzed public sentiment during the COVID-19 lockdowns, revealing valuable insights into public attitudes that could inform government policies.…”
Section: Literature Reviewmentioning
confidence: 99%